PERWUJUDAN EMPIRIS KULIAH KERJA NYATA (KKN): Studi Peningkatan Komunikasi dan Informasi Pelayanan Publik di Kelurahan Leuwinanggung - Agustian, Agustian; Julianti, Neneng; Wandatari, Rilanda; Amin, Muhammad; Jamaludin, Muhamad; Irnawati, Icoh; Mudofir, Mudofir; Sadari, Sadari; Khotimah, Husnul (Moderation | Journal of Islamic Studies Review, 2024)
Communication is very important for public services, especially in the government apparatus or bureaucracy. Public service information must be conveyed clearly and straightforwardly, so that there is no misunderstanding between the conveyor and recipient of information. As happened in Leuwinanggung Village, especially in RW 005, often public service information is not conveyed. As the KKN-T (Thematic Real Work Lecture) was carried out in Leuwinanggung Village, these problems began to be faced and corrected, with the creation of information boards (Mading). As the best means that has been chosen to improve the communication system of public service information. Therefore, the creation of an information board (Mading) has been carried out on February 24, 2024, and received a positive response from the RT/RW and the local community. Because one of the problems in the region has got a solution.